Graphene nanoribbons are internalized by human primary immune cell subpopulations maintaining a safety profile: A high-dimensional pilot study by single-cell mass cytometry. (December 2022) - Fuoco, Claudia; Luan, Xiangfeng; Fusco, Laura; Riccio, Federica; Giuliani, Giulio; Lin, Hazel; Orecchioni, Marco; Martín, Cristina; Cesareni, Gianni; Feng, Xinliang; Mai, Yiyong; Bianco, Alberto; et al.
Highlights: Graphene nanoribbons of different sizes have been functionalized with mass cytometry trackable 115 Indium through a straightforward method. Graphene nanoribbons showed high biocompatibility on peripheral blood mononuclear cells. Mass cytometry analysis revealed the capability of graphene nanoribbons to simulate myeloid dendritic cells and classical monocytes. Abstract: Graphene nanoribbons (GNRs) are emerging graphene materials showing clear promising applications in the biomedical field. The evaluation of GNR biocompatibility at the immune level is a critical aspect of their clinical translation. Here, we report the ex vivo immune profiling and tracking of GNRs at the single-cell level on eight human blood immune cell subpopulations. We selected ultra-small (GNRs-I-US) and small GNRs (GNRs-I-S), with an average length of 7.5 and 60 nm, respectively. GNRs were functionalized with 115 In to trace their cell interactions by single-cell mass cytometry. Both materials are highly biocompatible and internalized by immune cells without inducing significant functional changes. GNRs-I-US interacted to a greater extent with myeloid dendritic cells (mDCs) and classical monocytes, while GNRs-I-S mainly interacted with mDCs. These results demonstrate that structurally precise GNRs are efficiently internalized by immune cells. In addition, our chemical and methodological single-cell approach can be applied to other cell types using various carbon-based nanomaterials, bringing new insights into their safety and future biomedical applications. Graphical abstract: Two graphene nanoribbons of different length are functionalized with indium to follow their cell interactions using single-cell mass cytometry. These materials are internalized by immune cells without inducing significant functional changes, interacting with myeloid dendritic cells and classical monocytes. Our chemical and methodological approach can be applied to other types of cells using different nanomaterials, bringing novel understandings on their safety profile and future biomedical uses. Image, graphical abstract